FLIPGRID SEBAGAI MEDIA PEMBELAJARAN DAN PENGOPTIMALAN KETERAMPILAN BERPIDATO PERSUASIF SISWA SMP - Phroshak, Kresna Tribuana Putri (Hasta Wiyata, 2023)
To train student's speaking skills can be done through Bahasa Indonesia subject, which is by conveying ideas in persuasive speeches orally. It is necessary to support the subject by using a learning media such as Flipgrid. This media features short videos and discussion rooms to make studying more interesting and interactive. This media can motivate students to study deftly as well as hone their speaking skills. The purpose of this study was to determine the learning process and students’s speaking skills in persuasive speeches using Flipgrid. This research uses a qualitative descriptive approach with a case study research type. The subjects were 9th grade students of SMP Negeri 10 Malang, totaling 59 students. The research instruments are questionnaires, observation guidelines, test grids, and assessment rubrics. The results found that in the learning process using Flipgrid had a positive and negative impact on students. The positive impact makes learning more interactive and interesting. Meanwhile, the negative impact hinders the learning process because students do not have adequate laptops or phones to access the media. Then the results found in the students's speaking skills that as many as 20 students were at the very good qualification level, as many as 14 students were at the good qualification level, and no students were at the sufficient or less qualification level. From these results it was found that by persuasive speeches can hone students's learning skills so that they become confident, fully prepared, and fluent in speaking in front of many people